Land-use function evolution and eco-environmental effects in the tarim river basin from the perspective of production–living–ecological space - Wang, Yang; Wang, Yin; Xia, Tingting; Li, Yang; Li, Zhi (Frontiers in Environmental Science, 2022)
The coordinated development of production-living-ecological space (PLES) is a hot topic in territorial space planning. Based on remote sensing of PLES and statistical data of land use status in 2000, 2005, 2010, 2015 and 2020, this paper analyzes the evolutionary characteristics of land use function by using transfer matrix and gravity center transfer methods. These are combined with the eco-environmental quality index to reveal the driving factors of eco-environmental quality spatial differentiation in a geographic detector model. The results show that: (1) The structural evolution and regional differentiation of PLES are significant. The spatial distribution of production land, living land and ecological accommodation land is concentrated in Aksu City, Xayar County and other areas, showing an expanding trend. The key ecological spaces are mainly distributed in Hejing, Kuqa, Akto and Wuqia counties, showing an overall decreasing trend. The growth of production, living and ecological accommodation space comes from the occupation of key ecological space. (2) The center of gravity shift distance of production land is the greatest, followed by that of living land and key ecological land. The center of gravity shift distance of ecological accommodation land is the smallest. Improvement and deterioration trends for eco-environmental quality are high in the northwest and low in the southeast, and the spatial pattern evolution shows obvious agglomeration. (3) Different social activities have different impacts on ecological environment quality. For example, the implementation of ecological restoration projects and the progress afforded by scientific and technological innovation play a significant role in promoting the improvement of ecological environment quality. Conversely, the increase in population and the improvement in social consumption level aggravate the pressure on it.